2015
DOI: 10.1155/2015/347403
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Lymphonodular Cryptococcosis in an Immunocompetent Child

Abstract: We describe our experience with an apparently immunocompetent child presenting with pyrexia of unknown origin without focal signs. Investigations revealed lymphadenopathy at lung hila, mesentery, and porta hepatis. The child had received at least two months of empiric antituberculous therapy (ATT) before she came to us. A CT-guided biopsy revealed granulomatous inflammation. PAS stain showed yeasts which stained blue with Alcian blue, suggesting C. neoformans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…However, in our study, nearly 67.3% of patients had abdominal lymph nodes invasion, including of the mesentery, hepatic portal, and abdominal para-aortic lymph nodes, and some of them were accompanied with calcification, which is rarely reported [27]. Several cases presented with abdominal pain or discomfort were misdiagnosed as tuberculosis because abdominal cryptococcosis has similar symptoms or pathologic results as tuberculosis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, in our study, nearly 67.3% of patients had abdominal lymph nodes invasion, including of the mesentery, hepatic portal, and abdominal para-aortic lymph nodes, and some of them were accompanied with calcification, which is rarely reported [27]. Several cases presented with abdominal pain or discomfort were misdiagnosed as tuberculosis because abdominal cryptococcosis has similar symptoms or pathologic results as tuberculosis.…”
Section: Discussionmentioning
confidence: 62%
“…Besides lung and brain invasion, Dromer [ 26 ] demonstrated that the incidence of abdominal, renal, lymph node, and skin invasion (1.2%, 1.9%, 1.7%, and 0.4%, respectively) were lower than the results of the present study. However, in our study, nearly 67.3% of patients had abdominal lymph nodes invasion, including of the mesentery, hepatic portal, and abdominal para-aortic lymph nodes, and some of them were accompanied with calcification, which is rarely reported [ 27 ]. Several cases presented with abdominal pain or discomfort were misdiagnosed as tuberculosis because abdominal cryptococcosis has similar symptoms or pathologic results as tuberculosis.…”
Section: Discussionmentioning
confidence: 82%
“…Cough is also a reported symptom in pulmonary cryptococcal infection [15] . Similarly, radiological finding like abdominal lymphadenopathy, pulmonary cavitation, pleural effusion in active TB infection are nonspecific and have been reported in disseminated cryptococcal infection [16] . This implies that highly sensitive and specific diagnostic tests are required to rule out active TB in this high-risk population.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, a definitive microbiological TB diagnosis in patients with advanced HIV-associated cryptococcal meningitis patients is challenging. The most common form of TB in advanced HIV is extra-pulmonary TB; including abdominal, pleural, genitourinary and central nervous system [16] , [17] . With the exception of Tuberculous meningitis, other forms of extra pulmonary TB often require a tissue diagnosis, which may be challenging to obtain in resource poor settings.…”
Section: Discussionmentioning
confidence: 99%